2014
DOI: 10.1371/journal.pone.0101175
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Adenoidectomy on Pediatric Tympanostomy Tube Re-Insertions: A Population-Based Birth Cohort Study

Abstract: ObjectivesAdenoidectomy in conjunction with tympanostomy tube insertion for treating pediatric otitis media with effusion and recurrent acute otitis media has been debated for decades. Practice differed surgeon from surgeon. This study used population-based data to determine the protective effect of adenoidectomy in preventing tympanostomy tube re-insertion and tried to provide more evidence based information for surgeons when they do decision making.Study DesignRetrospective birth cohort study.MethodsThis stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…18 Adjunct adenoidectomy may enhance the effectiveness of ventilation tube insertion in OME patients and reduce the need for repeated ventilation tube insertion because of the removal of microbial reservoir and mechanical obstruction of the Eustachian tube. 16,17 The present study further demonstrated that adenoidectomy in children with OME may also improve their sleep quality, which was significantly disturbed, though the severity was less than the children with SDB because of relatively smaller tonsils.…”
Section: Discussionsupporting
confidence: 66%
“…18 Adjunct adenoidectomy may enhance the effectiveness of ventilation tube insertion in OME patients and reduce the need for repeated ventilation tube insertion because of the removal of microbial reservoir and mechanical obstruction of the Eustachian tube. 16,17 The present study further demonstrated that adenoidectomy in children with OME may also improve their sleep quality, which was significantly disturbed, though the severity was less than the children with SDB because of relatively smaller tonsils.…”
Section: Discussionsupporting
confidence: 66%
“…The risk of OME recurrence may be lower, and the time to subsequent TT placement may be significantly longer. The likelihood of subsequent TT placement is thought to be 40% lower in this context (Wang et al., 2014).…”
Section: Treatmentsmentioning
confidence: 99%
“…In children with AH and OME, the surgical removal of the adenoid (associated with ventilation tube insertion) accelerates the recovery of the middle ear mucosa, decrease the risk of recurrence and need of repetitive surgical procedures, and reduce treatment failure rate. However, new evidence point out that the benefits of adenoidectomy in children with OME older than 4 years-old is independently of the adenoid size [ 12 ], suggesting that the removal of a local reservoir of pathogenic microbiota (viruses, planktonic bacteria, and biofilms) is the key for such benefits [ 13 15 ]. Despite some studies have evaluated the microbial colonization of adenoid and middle ear, no studies have thoroughly studied the association of respiratory pathogenic microbiota between these two niches.…”
Section: Introductionmentioning
confidence: 99%